2012
DOI: 10.1111/j.1742-4658.2011.08448.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic glycoengineering through the mammalian GalNAc salvage pathway

Abstract: GalNAc is the initial sugar of mucin‐type O‐glycans, and is a component of several tumor antigens. The aim of this work was to determine whether synthetic GalNAc analogs could be taken up from the medium and incorporated into complex cellular O‐glycans. The cell line employed was CHO ldlD, which can only use GalNAc and Gal present in the medium for the synthesis of its glycans. All GalNAc analogs with modified N‐acyl groups (N‐formyl, N‐propionyl, N‐glycolyl, N‐azidoacetyl, N‐bromoacetyl, and N‐chloroacetyl) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…In addition, our accompanying paper (5) demonstrates that UDP-GlcNGc can also successfully enter the O-GlcNAcylation pathway resulting in O-GlcNGc modifications. We found GalNGc to be incorporated into O-glycans as also reported very recently by another group (36,37). Going beyond these published reports, we also isolated cellular O-glycans from cells grown in the presence of either GalNAc or GalNGc and performed structural analyses using mass spectrometry.…”
Section: Exogenous Galngc Incorporates As Glcngc Into Cellularsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, our accompanying paper (5) demonstrates that UDP-GlcNGc can also successfully enter the O-GlcNAcylation pathway resulting in O-GlcNGc modifications. We found GalNGc to be incorporated into O-glycans as also reported very recently by another group (36,37). Going beyond these published reports, we also isolated cellular O-glycans from cells grown in the presence of either GalNAc or GalNGc and performed structural analyses using mass spectrometry.…”
Section: Exogenous Galngc Incorporates As Glcngc Into Cellularsupporting
confidence: 84%
“…Future studies will reveal the impact of media supplemented GalNAc derivatives onto the overall complexity of O-glycan structural diversity in cells. After this study was finalized, another research group showed predominantly by lectin binding analyses that various artificial GalNAc derivatives, including GalNGc, seem to incorporate into O-glycans via the GalNAc salvage pathway (36,37).…”
Section: Exogenous Galngc Incorporates As Glcngc Into Cellularmentioning
confidence: 99%
See 1 more Smart Citation
“…(1 2)-Linked nonamannoside TOF Use of ionic liquid support for the synthesis of large and complex oligosaccharides (Ma et al, 2011a) N-O-linked glycans MALDI Use of glycosyl ortho-hexynylbenzoates as donors under the catalysis of PPh3AuOTf O-Glycans with unnatural GalNR groups TOF Use of CHO IdID cell line fed with GalNR molecules so that they could be incorporated into O-glycans (Pouilly et al, 2012a) Oligosaccharides TOF (DHB) New method for regioselective glycosylation employing saccharide oxyanions (Matwiejuk & Thiem, 2011) Oligosaccharides TOF C5-acetamide sialic acid donor for -selective (Uchinashi et al, sialylation 2011) Oligosaccharides TOF/TOF (DHB)…”
Section: R-tof (Thap)mentioning
confidence: 99%
“…As a result of the growing knowledge on signaling and metabolic pathways in mammalian cells, pathway engineering approaches have recently been extended to mammalian cells [160-162]. It has also been considered for tissue engineering and regenerative medicine applications [163].…”
Section: Cell Sources and Controlling Cell Behaviormentioning
confidence: 99%